2017
DOI: 10.1038/nature21024
|View full text |Cite
|
Sign up to set email alerts
|

Subcycle quantum electrodynamics

Abstract: 2Coherent states represent the closest counterpart to a classical electromagnetic wave that exists in quantum electrodynamics. The quantum noise amplitudes of their electric and magnetic fields coincide precisely with those of the vacuum state 19 . Recently, we have succeeded to directly detect the bare vacuum fluctuations of the mid-infrared electric field with highly sensitive electro-optic sampling based on ultrashort laser pulses 15,16 . One key aspect of this technique is that it operates out of a time-do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 31 publications
0
96
0
Order By: Relevance
“…Such a system would, e.g., enable the deterministic creation of biphotons and eventually ultrashort wavepackets with well-defined photon numbers via multiple single-photon amplification processes. Also, working with QDs resonant to the mid-infrared spectral range would provide ultrafast emitters and amplifiers producing nonclassical states of light that could be directly read out in the time domain with ultrabroadband quantum sampling of the electric field [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Such a system would, e.g., enable the deterministic creation of biphotons and eventually ultrashort wavepackets with well-defined photon numbers via multiple single-photon amplification processes. Also, working with QDs resonant to the mid-infrared spectral range would provide ultrafast emitters and amplifiers producing nonclassical states of light that could be directly read out in the time domain with ultrabroadband quantum sampling of the electric field [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…New developments in ultra-stable few-cycle laser sources and advanced detection techniques have paved the way for the generation of few-cycle pulses of mid-infrared (MIR) squeezed light and the electro-optic detection of their electric field statistics with subcycle temporal resolution [16][17][18]. The subcycle features in the noise patterns of the generated quantum fields are due to the spatio-temporal modulation of the refractive index of the NX induced by the driving field [18]. This is analogous to a time-dependent metric for the space-time occupied by the electric field, which leads to photon creation in the perspective of a moving observer [19].The spectral properties of ultrabroadband squeezed states are also of particular interest because they can elucidate connections between quantum gravitational effects and their table-top optical analogues.…”
mentioning
confidence: 99%
“…(17) for the Lorentz dielectric function in Eq. (5). DISCUSSION We have demonstrated that a measure of the timecorrelations of QVF, once normalised over the uncoupled free-space vacuum result, provides us access to the same set of observables which we can measure with a linear optical characterisation of the sample.…”
Section: Qvf In Dispersive Mediamentioning
confidence: 84%
“…[30] it is shown that for a medium described by Eq. (5), N k doesn't present any resonant behaviour. This is clearly at odd with the results in Fig.…”
Section: Qvf In Dispersive Mediamentioning
confidence: 92%